2015
DOI: 10.1126/science.1260943
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary changes in promoter and enhancer activity during human corticogenesis

Abstract: Human higher cognition is attributed to the evolutionary expansion and elaboration of the human cerebral cortex. However, the genetic mechanisms contributing to these developmental changes are poorly understood. We used comparative epigenetic profiling of human, rhesus macaque and mouse corticogenesis to identify promoters and enhancers that have gained activity in humans. These gains are significantly enriched in modules of co-expressed genes in the cortex that function in neuronal proliferation, migration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
314
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(377 citation statements)
references
References 44 publications
(32 reference statements)
21
314
5
2
Order By: Relevance
“…For example, combined analysis of human and chimpanzee gene expression data and sequences suggested that pain perception and nociception may have changed in humans through differential regulation of opioid signaling (Cruz-Gordillo et al, 2010). Comparative epigenetic profiling of human, rhesus macaque and mouse corticogenesis revealed promoters and enhancers that have gained activity during human evolution (Reilly et al, 2015), although the sequence differences driving these changes are yet to be identified. Similar The gene FOXP2 is one of the most extensively studied examples of a uniquely human genome sequence.…”
Section: The Next-generation Sequencing Eramentioning
confidence: 99%
See 1 more Smart Citation
“…For example, combined analysis of human and chimpanzee gene expression data and sequences suggested that pain perception and nociception may have changed in humans through differential regulation of opioid signaling (Cruz-Gordillo et al, 2010). Comparative epigenetic profiling of human, rhesus macaque and mouse corticogenesis revealed promoters and enhancers that have gained activity during human evolution (Reilly et al, 2015), although the sequence differences driving these changes are yet to be identified. Similar The gene FOXP2 is one of the most extensively studied examples of a uniquely human genome sequence.…”
Section: The Next-generation Sequencing Eramentioning
confidence: 99%
“…Comparative studies at the molecular and cellular level, therefore, have been mainly based on analysis of preserved tissues from different adult organs (frequently postmortem) or immortalized cell lines (Romero et al, 2012;Schmidt et al, 2010;Zhou et al, 2014). Human embryonic tissues and cells have also occasionally been utilized, for example in the characterization of HAR1 (Pollard et al, 2006b) and SRGAP2 (Charrier et al, 2012;Dennis et al, 2012), and for comparative epigenetic profiling (Reilly et al, 2015). However, the chimpanzee samples necessary for determining whether observed differences are human specific are not available.…”
Section: The Era Of Human Development In a Dishmentioning
confidence: 99%
“…Reilly et al (2015) have recently identified thousands of regulatory elements involved in the formation of the neocortex during the first weeks of human embryonic development, which however do not display such activity in rhesus macaque brains. Another remarkable example is the finding that a human CNE regulating the expression of a neurodevelopmental gene, when inserted in the mouse genome, leads to a 12% increase in brain size in mice, whereas the chimpanzee version of such element does not (Boyd et al 2015).…”
Section: Non-coding Regulatory Elementsmentioning
confidence: 99%
“…Hence, potential evolutionary modifications of enhancer activities have been the subject of intense investigation in the field of regulatory evolution. For example, using ChIP-seq for histone H3 lysine 27 acetylation (H3K27Ac), an active enhancer mark, the evolutionary and developmental dynamics of enhancer activities have been mapped in various different organs and across several taxonomic ranks [68][69][70]. Ideally, such enhancer activity maps will be complemented by the binding profiles of transcription factors known to be important for the development or function of the tissues in question [71,72].…”
Section: Homology Assessment: Gene Expression and Regulatory Strategiesmentioning
confidence: 99%